Faktor-faktor yang Mempengaruhi Kinerja Sistem Informasi yang Digunakan pada Instansi Pemerintah - Lilis Endang Wijayanti; Ag Kristianto Pw; Vera Desy Nurmalia (INVENTORY: JURNAL AKUNTANSI, 2022)
Government agencies are increasingly sophisticated by using various information systems for services to the community and to facilitate the completion of work. Badan Keuangan dan Aset Daerah(BKAD) in the DIY region uses various information systems. The use of online-based applications is expected to facilitate work and improve service quality. Various applications used in one agency raise the question, how is the performance of the application or information system? Does the information system used meet the user's wishes? This study analyzes the performance of information systems from the user's point of view. The analysis is done by testing the factors that affect the performance of the information system. The factors tested are Personal Technical Skills, Top Management Support, Quality of Human Resources and Education and Training. The object of research is the Integrated Information System used in BKAD in the DIY Province. Data were obtained by distributing questionnaires to SIMPADU users. The number of respondents who participated in this study were 110 respondents. The data is processed by Moderating Regression Analysis. The results of data processing show that the quality of human resources affects the performance of information systems. Personal Technical Skills and Top Management Support do not influence Information System performance. Education and Training variables are proven to moderate the relationship between the variables of Personal Technical skills, Top Management Support and HR Quality. Education and Training strengthens the relationship between Personal Technical Skills and Top Management Support. However, the Education and Training variable weakens the relationship between the HR Quality variable and the Information System Performance.